Effect of the Addition RecombinantGiant Grouper Growth Hormone (rElGH) on Feed Towards Growth Performance and Survival Rate of Fish Seed Slice (Ompok hypopthalmus) - Rohmat Supriyanto; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The aim of research was to assess the added effect of recombinantEpinepheluslanceolatus GrowthHormone (rElGH) on feed toward the growth performance and survival rate of fish seed slice (Ompokhypopthalmus). Culture vessel in the form of net bags of 1 x 1 x 1 meters of 20 bags with stocking density of 30 fish/m3.This research was using experimental method by completely random design (RAL) one factor with five treatments and four replications. The treatments were :P0= rElGH 0 mg/kg of feed, P1= rElGH 6 mg/kg of feed, P2= rElGH 12 mg/kg of feed, P3= rElGH 18 mg/kg of feedand P4= rElGH 24 mg/kg of feed. The results showed that the combination of rElGH in feed, showed highly significant effect (P<0.05) of the total weight, total length, specific growth rate, feed conversion ratio, and no significant effect (p>0.05) to survival rate. value growth and the level of the best survival was found in treatment P2 with a value weight total: 3,85±0,46 gram, length total: 3,60±0,15 cm, specific growth rate: 5,56±0,32% per day, feed conversion ratio: 1,10±0,12 and survival rate: 100 ± 0.00%. Keywords: Fish Slice, recombinantEpinepheluslanceolatus Growth Hormone, Growth